Perspectives Towards Life among the Survivors of Oral Cancer Patients (Medical Forum Monthly, 2022)
Objective: To identify the psychosocial problems faced by oral cancer survivors and to assess their health-related quality of life.Study Design: descriptive Cross-Sectional studyPlace and Duration of Study: This study was conducted at the Nuclear Institute of Medicine and Radiotherapy Jamshoro, from Nov 2017 to Feb 2018.Materials and Methods: Patients above 18 years of age successfully treated for Oral Cancer were included by Non probability convenience sampling. Level of anxiety and depression was accessed by using the Diagnostic and Statistical Manual of Mental Disorders (IV codes). Data was analyzed by using SPSS version 24.Results: According to the data anxiety outcome was divided in 05 grades. Moderate anxiety was very common in participants (47.2%), mildly anxious were (31.2%), severe anxiety in (14.4%) and (0.8%) were extremely anxious, remaining (6.4%) shown no anxiety. Regarding HRQOL (40.8%) survivors reported to have good HRQOL as they had full family/friends support, (48.8%) survivors responded an average HRQOL as they had partial family/friends support, and (10.4%) survivors were having very poor quality of life as they had meager support.Conclusion: It was concluded in our study that almost all patients experience psychological issues after treatment of Oral Cancer. Special care and attention is required to them, continues counseling and support can help in improving quality of life.